Sustaining the burden”: a qualitative study on the emotional impact and social functioning of family caregivers of patients with psychosis - Villena Jimena, Amelia; Morales-Asencio, José Miguel; Quemada-González, Casta; Hurtado, María M. (Elsevier, 2024)
Evidence shows that caring for a family member with a psychotic disorder generates a significant emotional impact and repercussions on social functioning. However, this caregiving experience can be influenced by cultural factors. The aim of this study is to explore the experience and perception of a group of family caregivers of patients with psychotic disorders of different durations regarding the emotional and social functioning repercussions of caregiving on them in Andalusia. Three focus groups (28 participants) were conducted. Data were subject to a thematic analysis. Three themes emerged from the data: 1) Emotional invasion; 2) Disruption in the caregiver's life project; and 3) Changes in the family system. Participants reported experiencing sadness, fear, overwhelm, hopelessness, and uncertainty. Caregivers' accounts reflected an interruption of their daily tasks, as well as the need to reformulate plans or goals outside the family life that require long-term commitment, such as professional development or even their residence. The narratives indicated an impact on all roles within the family system, particularly for the mother. The results are consistent with existing research. Healthcare professionals and programs should take into account the costs associated with caregiving in order to minimize them, given the impact it has on both the patient's and the caregivers' health.
Keywords: Enfermos mentales - Relaciones familiares; Cuidados de larga duración; Fatiga mental; Family caregivers; Psychoses; Burden of care